Optimal Resource Key Management Protocol for Clustered Heterogeneous Wireless Sensor Networks - Kavitha, T.; Sridharan, Dr.D. (Malaysian Journal of Computer Science, 2013)
Secure communication in a Wireless Sensor Network (WSN) can be achieved through efficient key management techniques. Achieving security is not so simple due to the limited capability of radio module in wireless sensor network device. The probabilistic model provides a flexible and efficient solution when comparing various key distribution schemes developed so far. Here, we propose an Optimal Resource Key Management Protocol (ORKMP) considering the limited capabilities of WSN for a Clustered Heterogeneous Wireless Sensor Network (CHWSN) which follows a hierarchy. Better performance and scalable security solutions can be achieved by heterogeneous sensor nodes. The sensor nodes are deployed in groups, each controlled by a cluster head, which leads to less communication overhead. The keys distributed to nodes are based on the probabilistic model which combines the deployment knowledge with the sensor node’s attributes of signal range and state. This hybrid effect reduces the memory requirement, by sustaining high connectivity and resilience. On the whole, the proposed key management protocol provides an efficient security solution with optimum resource requirement.